Patient-reported outcome measures in the care of in-centre hemodialysis patients - Sara N. Davison; Scott Klarenbach; Braden Manns; Kara Schnick-Makaroff; Robert Buzinski; Bonnie Corradetti; Hilary Short; Jeffrey A. Johnson (SpringerOpen, 2021)
Abstract Kidney failure requiring dialysis is associated with high symptom burden and low health-related quality of life (HRQL). Patient-reported outcome measures (PROMs) are standardized instruments that capture patients' symptom burden, level of functioning, and HRQL. The routine use of PROMs can be used to monitor aspects of patients' health that may otherwise be overlooked, inform care planning, and facilitate the introduction of treatments. Incorporating PROMs into clinical practice is an appropriate strategy to engage patients and enhance their role in decisions regarding their care and outcomes. However, the implementation of PROMs measurement and associated interventions can be challenging given the nature of clinical practice in busy hemodialysis units, the variations in organization and clinical workflow across units, as well as regional programs. Implementing PROMs and linking these with actionable treatment aids to alleviate bothersome symptoms and improve patients' wellbeing is key to improving patients' health. Other considerations in implementing PROMs within a hemodialysis setting include integration into electronic medical records, purchase and configuration of electronic tools (i.e., tablets), storage and disinfection of such tools, and ongoing IT resources. It is important to train clinicians on the practical elements of using PROMs, however there is also a need to engage clinicians to use PROMs on an ongoing basis. This article describes how PROMs have been implemented at in-centre hemodialysis units in Alberta, Canada, addressing each of these elements.